KONSEPSI HUKUM PERDATA INTERNASIONAL DALAM HAK PENGANGKATAN ANAK DI INDONESIA - Iffan, Ahmad (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2023)
Child adoption is one of the ways that some families want to complete their families. In international adoption there are two global international conventions on child adoption, namely The Hague Convention on the Protection of Children and Co-operation in Respect of Inter-Country Adoption 1993 (The Hague Convention 1993) and The Hague Convention on the Juridiction and Applicable Law and Recognition of Decrees Relating to Adoption 1965 (The Hague Convention 1965). There are legal consequences in the legal consequences of international child adoption on the adopted child, namely legal consequences on the legal relationship between adopted children, legal consequences on alimony rights and legal consequences on inheritance and guardianship rights. the conception of child adoption by hpi is also refined by the provisions contained in civil law and Islamic law regarding child adoption.